ANALISIS KOMITMEN AFEKTIF PEGAWAI DINAS PERHUBUNGAN KOTA SEMARANG - Putri Wulan Septia Ningrum; Endah Winarti; Harnoto . (LPPM STIE DHARMAPUTRA SEMARANG, 2018)
AbstractThe purpose of this research is to analyze the influence of motivation of justice and emotional intelligence on affective commitment with career satisfaction as mediation variable. The population of this study is all employees of Department of Transportation Semarang city, amounting to 225 people. The samples taken as many as 144, while that can be processed as many as 133 people. Data processing method is using SPSS. The results of hypothesis testing show that the motivation of justice has a positive and significant effect on career satisfaction, the higher the motivation of justice, the higher the career satisfaction. Emotional intelligence has a positive and significant effect on career satisfaction, the higher the emotional intelligence, the higher the career satisfaction. Career satisfaction has a positive and significant effect on affective commitment, the higher the satisfaction of the career, the higher the affective commitment. Motivation of justice has a positive and significant effect on affective commitment, the higher the motivation of justice, the higher affective commitment. Emotional intelligence has a positive and significant effect on affective commitment, the higher the emotional intelligence, the higher affective commitment. Keywords: Motivation of Justice, Emotional Intelligence, Career Satisfaction, Affective Commitment AbstrakTujuan penelitian ini adalah untuk menganalisis pengaruh motivasi keadilan dan kecerdasan emosional terhahap komitmen afektif dengan kepuasan karier sebagai variabel mediasi. Populasi dari penelitian ini adalah seluruh pegawai Dinas Perhubungan Kota Semarang yang berjumlah 225 orang. Adapun sampel yang diambil sebanyak 144, sedangkan yang bisa diolah sebanyak 133 orang. Metode pengolahan data menggunakan SPSS. Hasil pengujian hipotesis menunjukan bahwa motivasi keadilan berpengaruh positif dan signifikan terhadap kepuasan karier, semakin tinggi motivasi keadilan maka semakin tinggi kepuasan karier. Kecerdasan emosional berpengaruh positif dan signifikan terhadap kepuasan karier, semakin tinggi kecerdasan emosional maka semakin tinggi kepuasan karier. Kepuasan karier berpengaruh positif dan signifikan terhadap komitmen afektif, semakin tinggi kepuasan karier maka semakin tinggi komitmen afektif. Motivasi keadilan berpengaruh positif dan signifikan terhadap komitmen afektif, semakin tinggi motivasi keadilan maka semakin tinggi komitmen afektif. Kecerdasan emosional berpengaruh positif dan signifikan terhadap komitmen afektif, semakin tinggi kecerdasan emosional yang dilakukan maka semakin tinggi komitmen afektif. Kata kunci: Motivasi Keadilan, kecerdasan emosional, kepuasan karier, komitmen afektif